Effect of temperature on the extraction of bio-oil from oil palm mesocarp fiber using supercritical CO2 - Mohamed, M. (Penerbit UTM Press, 2014)
This paper highlights the conversion of oil palm mesocarp fiber into bio-oil via SFE. Effects of extraction temperature which are temperature within 60-90°C are investigated for two hours of extraction time. The yield is diluted in 10ml dichloromethane (DCM) for analysis of gas chromatography-mass spectrometry (GC-MS). The extracted bio-oil is found to contain fatty acid, esters and other long chain hydrocarbon. The concentration of these compounds is determined based on chromatogram peak area. The analysis indicates that fatty acid such as 6-octadecanoic acid (stearic acid), n-hexadecanoic acid (palmitic acid) and dodecanoic acid, 1,2, 3-propanetryl ester (glycerol trilaurate), are the major compounds of the extracted bio-oil. The extraction yield increased from 16.7 to 19.8 once the temperature was increased from 60 to 90°C. Concentration of palmitic acid constantly decreased with temperature. Inversely, myristic acid concentration constantly increased with temperature. However, concentration of glycerol trylaurate, stearic acid and lauric acid was not significantly affected by temperature. Concentration of stearic acid and lauric acid was first reduced once temperature increased from 60 to 70°C yet increased at 90°C and vice versa observation for glycerol trilaurate. © 2014 Penerbit UTM Press. All rights reserved.